Inheritance of resistance to aphid in cowpea - Bata, H.D.; Singh, B.; Singh, S.R.; Ladeinde, T.A.O. (1987)
Aphid (Aphis craccivora Koch) is a major pest of cowpea [Vigna unguiculata (L.) Walp.] particularly in the drier regions of the tropics. It causes direct damage by feeding on the plants and also transmits viruses. Several sources of resistance to cowpea aphid have been identified and efforts are underway to develop aphid-resistant cultivars of cowpea. This study was undertaken to elucidate the inheritance of resistance to aphid in cowpea. Three resistant lines were used in the study. Parental, F1, F2, F3, and backcross populations involving resistant ✕ susceptible and resistant ✕ resistant lines were evaluated in the greenhouse using artificial infestation with aphids. The F1 plants in all the crosses were resistant and the F2 populations derived from all the crosses involving resistant and susceptible parents segregated into 3 resistant:1 susceptible ratio. The backcross populations involving susceptible parents segregated into 1 resistant:1 susceptible ratio, whereas the backcross populations involving resistant parents were completely resistant. The F3 progenies derived from resistant F2 plants showed a ratio of 1/3 true breeding resistant:2/3 segregating like F2's. These data indicated monogenic dominant inheritance of aphid resistance. The gene symbol Rac (resistance to Aphis craccivora) is being assigned for this trait.